(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті розкрито особливості організації роботи учнів основної школи з краєзнавчим матеріалом на уроках географії. Подано зразки інтерактивних технологій, що сприяють ефективному засвоєнню нового матеріалу на міжпредметній основі. Ключові слова: учні основної школи, географія, краєзнавство. In the article the characteristics of the organization of primary school students with local history material. Examples of the interactive technologies that promote assimilation of new material on the interdisciplinary basis. Key words: elementary school students, geography, and ethnography.